Pengembangan Pop Up Book Eksis Pada Tema 5 Sub Tema 2 Di Kelas V SDN Buluh 1 - Asha Novia Anggraini; Conny Dian Sumadi (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
This study uses the development method with the ADDIE model. The subjects of this study were 14 students in class V at SDN Buluh 1 for the 2022/2023 academic year. The validity results were obtained from an average media expert validation of 94.73%, learning device design 88%, and material 97% with the third category of expert validation being declared very valid. The attractiveness result was obtained through the small group test student response rate obtained by a value of 97.77%, and the field test student response rate was obtained by 95.15% with a very interesting category. Effectiveness results were obtained through observing teacher activities, namely an average proportion of 90%, observations of student activities with an average proportion of 90.90% with the active category, as well as student learning outcomes tests obtained by 11 students who were declared complete with scores above KKM 65 and classically student learning completeness obtained a proportion of 100% complete. Based on the data above, the pop up book eksis media is declared valid, interesting, and effective for use in teaching and learning activities in class V SDN Buluh 1.